Advances in bridge maintenance, safety management, and life-cycle performance : proceedings of the Third International Conference on Bridge Maintenance, Safety and Management, 16-19 july 2006, Porto, Portugal - IABMAS '06 /: proceedings of the Third International Conference on Bridge Maintenance, Safety and Management, 16-19 july 2006, Porto, Portugal - IABMAS '06. (2015) - Unknown
No abstract available